Amblyomma triste (Koch, 1844) (Acari : Ixodidae): Morphological description of the ovary and of vitellogenesis - de Oliveira, P. R.; Mathias, Maria Izabel Camargo [UNESP]; Bechara, G. H. (Elsevier B.V., 2006)
The present study presents the morphology, histology, and the dynamics of vitellogenesis in females of the tick Amblyomma triste. The ovary in this species is of the panoistic type, therefore it lacks nurse cells. It is composed of a layer of epithelial cells that outwardly form the wall of the ovary, but also originate the pedicel, the structure that attaches the oocytes to its external margin, as well the oocytes themselves. In Amblyomma triste, the oocytes develop in four synchronic stages, which differs from the process in other tick species. The classification of the stages of the oocytes was carried out based on the presence of four morphologic characteristics: cytoplasm appearance; site of the germ vesicle; presence, quantity, and constitution of the yolk granules and presence of chorium. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Amblyomma triste; tick; ovary; vitellogenesis; histology